Randomised control trial of virtual reality in cognitive rehabilitation: effectiveness and near-transfer effect for stroke patients - Jovita Janavičiūtė-Pužauskė; Raimonda Petrolienė; Loreta Zajančkauskaitė-Staskevičienė; Andrius Paulauskas; Liuda Šinkariova (BMC Psychology)
Abstract Background This study aims to determine whether cognitive training based on an egocentric perspective leads to greater improvements in target functions compared to training using an allocentric perspective or conventional rehabilitation. Additionally, it seeks to examine whether egocentric perspective-based training enhances the near transfer effect, resulting in improved other cognitive functions compared to allocentric perspective-based training and conventional rehabilitation. Methods 132 stroke patients (65.9% males) aged 31 to 83 (mean age 62.54 ± 10.62) undergoing inpatient rehabilitation were randomly assigned to one of the three groups: allocentric (N = 40) or egocentric perspective-based (N = 46) selective visual attention and short-term visual memory training and control (conventional rehabilitation) group (N = 46). Evaluations were performed before (at the beginning of rehabilitation for control group) and after the intervention (two weeks after pre-test for control group). The target functions included the changes in short-term visual memory, visual-spatial attention, attention-orientation, while near transfer effect included the changes in visuo-construction abilities, task switching, verbal memory, verbal fluency, language, visuo-spatial abilities, general cognitive function. To investigate how different perspectives affect selective visual attention and short-term visual memory training and near-transfer effect over time, while accounting for baseline cognitive scores, were conducted mixed repeated measures ANOVA and ANCOVA (controlled for age, years of education, lesion location, and days since stroke). A priori power analysis and effect sizes using Cohen’s dz for matched pairs were calculated. Results The results showed that cognitive rehabilitation tasks based on egocentric perspective in combination to conventional rehabilitation are effective in improving attention-orientation and cause near transfer effect on spatial abilities and general cognitive functioning. While tasks based on allocentric perspective in combination to conventional rehabilitation are effective in improving short-term visual memory and cause near transfer effect on spatial abilities. Conclusions The cognitive improvements and near-transfer effects observed in our results indicate that combining conventional rehabilitation with tasks based on egocentric and allocentric perspectives integrated in virtual reality environments can enhance rehabilitation effectiveness. However, further studies are required to confirm the generalizability of these findings. Trial registration The present study, along with its protocol, was retrospectively registered in the ISRCTN clinical trial registry on January 3, 2024 ( https://doi.org/10.1186/ISRCTN14922230 ).